2014
DOI: 10.1371/journal.pone.0092926
|View full text |Cite
|
Sign up to set email alerts
|

Src Is Required for Mechanical Stretch-Induced Cardiomyocyte Hypertrophy through Angiotensin II Type 1 Receptor-Dependent β-Arrestin2 Pathways

Abstract: Angiotensin II (AngII) type 1 receptor (AT1-R) can be activated by mechanical stress (MS) without the involvement of AngII during the development of cardiomyocyte hypertrophy, in which G protein-independent pathways are critically involved. Although β-arrestin2-biased signaling has been speculated, little is known about how AT1-R/β-arrestin2 leads to ERK1/2 activation. Here, we present a novel mechanism by which Src kinase mediates AT1-R/β-arrestin2-dependent ERK1/2 phosphorylation in response to MS. Differing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 35 publications
0
22
1
Order By: Relevance
“…Src is activated by dephosphorylation of tyrosine residue at the C terminal to unfold the protein followed by tyrosine residue phosphorylation. The Src family members Fyn, Lyn, and c-Src play a key role in the signaling in response to mechanical stretch (1,43,44,49,64). For example, in vascular smooth muscle cells (VSMC), mechanical stretchinduced phosphoinositide 3-kinase (PI3-K)/protein kinase B (Akt), p21ras, and ERK1/2 activation has been suggested to be mediated at least in part by Src since pharmacological inhibition or overexpression of a kinase-dead c-Src mutant blocked these effects (26,56).…”
Section: Discussionmentioning
confidence: 99%
“…Src is activated by dephosphorylation of tyrosine residue at the C terminal to unfold the protein followed by tyrosine residue phosphorylation. The Src family members Fyn, Lyn, and c-Src play a key role in the signaling in response to mechanical stretch (1,43,44,49,64). For example, in vascular smooth muscle cells (VSMC), mechanical stretchinduced phosphoinositide 3-kinase (PI3-K)/protein kinase B (Akt), p21ras, and ERK1/2 activation has been suggested to be mediated at least in part by Src since pharmacological inhibition or overexpression of a kinase-dead c-Src mutant blocked these effects (26,56).…”
Section: Discussionmentioning
confidence: 99%
“…The β 2 -adrenergic receptor was specifically demonstrated to activate the anti-apoptotic protein Bcl2 via the ERK pathway [27] and both were up-regulated in E2F6-Tg myocardium. In other studies it was demonstrated that the induction of ERK via β 2 -AR was dependent on c-Src which is also activated in E2F6-Tg mice and can be induced via mechanical stretch such as that imposed by dilation [31,42,43]. Thus the activation of β 2 -AR, c-Src, ERK, and Bcl2 may reflect the attempt of E2F6-Tg myocardium to mount a survival signal following the stress of cardiac dilation which is not related to growth, hence the lack of significant hypertrophy in these mice.…”
Section: Discussionmentioning
confidence: 94%
“…E2F6 Tg mice also presented with increased activation of c-Src which is most likely due to phosphorylation by Gα in response to adrenergic stimulation [29]. c-Src can activate the mitogen activated protein kinase signaling pathway via the Ras family of small GTPases and β-arrestin resulting in an increase in ERK activity associated with cardiac growth [30,31]. Thus E2F6 expression stimulated the pro-hypertrophic β 2 -adrenergic signaling pathway resulting in PKA and c-Src/ERK activation, but without the expected increase in cardiac muscle mass.…”
Section: Discussionmentioning
confidence: 99%
“…35, 36 We recently also confirmed that β-arrestin2-dependent Src activation is a prerequisite for mechanical stretch-induced ERK1/2 phosphorylation. 31 The AT1-R stimulates tyrosine phosphorylation of the Janus family kinases (Jak1, Jak2, Jak3, and Tyk2). 12 Both AngII and mechanical stretch activate the AT1-R to induce the physical association and activation of Jak2, resulting in the phosphorylation of signal transducers and activators of transcription (STAT) proteins, which translocate to the nucleus and activate gene transcription.…”
Section: Mechanical Stress Activates At1-r Without the Involvement Ofmentioning
confidence: 99%
“…60 Our recent study also indicated that mechanical stretch-induced ERK1/2 activation in a β-arrestin2/Src-dependent and G protein-independent manner. 31 Recent work in animal models of heart failure suggests…”
Section: Arb Developmentmentioning
confidence: 99%